Concept of headhunting in the ancient Ao Naga society - Pandey, R.; Ismagulova, S. (Journal of Oriental Studies, 2022)
Until the mid of the 19th century, the Ao tribes had lived isolated from foreign political influence and practiced “headhunting” for thousands of years. In most cases, this horrendous practice was understood as a senseless and accidental “cutting off someone’s head” for some reason or even for no reason. Nevertheless, the “headhunting” practice was a method of defense and attack, which had constituted a tradition in Ao Naga military tactics. The safety of the villagers depended entirely on the level of military training of the tribe’s male population. In other words, for the Naga tribes, who represented sociopolitical units in a monarchical structure, the practice of “headhunting” meant not only self-defense from the hostile tribes, but also as a mechanism for survival. However, the practice has become only a symbol of the past Naga history for the modern generations today that entirely have converted to Christianity. Key words: Headhunting, the Ао Nagas, Aren, Ariju, tribal custom, traditional society.